Vote choice and legacies of violence: Evidence from the 2014 colombian presidential elections (2015)
Elections are regularly held in countries facing ongoing civil conflicts, including in India, Iraq, Nigeria, the Philippines, and Ukraine. Citizens frequently go to the polls having endured years of violence between armed groups and governments. A growing literature questions how violence conditions voters’ support for incumbents versus challengers, and for hawks versus doves. We analyze this relationship in the context of the 2014 presidential election in Colombia, an election defined by candidates’ positions on negotiations with the country’s largest insurgent group, the FARC. Our results show an inverted-U relationship between past insurgent violence and vote share for President Juan Manuel Santos, the pro-peace candidate: he performed better in communities with moderate levels of insurgent violence and poorly in communities with both very high and very low violence. We also find that areas where the FARC originally mounted attacks 50 years ago more strongly supported Santos. The article concludes by comparing these results with past studies of violence and vote choice in Israel, Turkey, and Spain. © The Author(s) 2015.